2013
DOI: 10.1160/th12-09-0655
|View full text |Cite
|
Sign up to set email alerts
|

Both NF-κB and c-Jun/AP-1 involved in anti-β2GPI/β2GPI-induced tissue factor expression in monocytes

Abstract: Our previous data has demonstrated that Toll-like receptor 4 (TLR4) and its signalling pathway can contribute to anti-β2-glycoprotein I/β2-glycoprotein I (anti-β2GPI/β2GPI) -induced tissue factor (TF) expression in human blood monocytes and acute monocytic leukaemia cell line THP-1. However, its downstream nuclear transcription factors have not been well explored. In the current study, we further investigated whether nuclear factor kappa B (NF-κB) and activator protein (AP-1) were activated and their roles in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 40 publications
1
17
1
Order By: Relevance
“…Another MAPK, JUN1/2, was also activated in this process (Zhou et al, 2012). A major discrepancy between the findings reported by Lopez-Pedrera et al (2006) and our results is that we found NF-jB activity can be regulated by several upstream kinases including p38, JNK and ERK (Xia et al, 2013). In contrast to the above-mentioned researches, Bohgaki et al (2004) showed that neither ERK nor JNK pathway was activated through activation of aPL/b2GPI in monocytes.…”
Section: Open Questionscontrasting
confidence: 99%
See 1 more Smart Citation
“…Another MAPK, JUN1/2, was also activated in this process (Zhou et al, 2012). A major discrepancy between the findings reported by Lopez-Pedrera et al (2006) and our results is that we found NF-jB activity can be regulated by several upstream kinases including p38, JNK and ERK (Xia et al, 2013). In contrast to the above-mentioned researches, Bohgaki et al (2004) showed that neither ERK nor JNK pathway was activated through activation of aPL/b2GPI in monocytes.…”
Section: Open Questionscontrasting
confidence: 99%
“…We further investigated whether nuclear NF-jB and AP-1 were activated through anti-b2GPI/b2GPI complex induced-TF expression and regulated by MAPKs and found that treatment of the cells with anti-b2GPI/b2GPI complex could markedly increase the levels of phosphorylated NF-jB (p-NF-jB p65; RelA) and c-Jun (JUN)/AP-1 (p-c-Jun), as well as TF expression (Xia et al, 2013). Both NF-jB inhibitor, pyrrolidine dithiocarbamate (PDTC), and the AP-1 inhibitor, curcumin, could attenuate TF expression induced by anti-b2GPI/b2GPI or APS-IgG/b2GPI complex.…”
Section: Review ª 2013 John Wiley and Sons Ltdmentioning
confidence: 99%
“…Among the important signaling intermediates that play a central role in this process are proximal mediators of innate responses, such as NF-kB [80][81][82], p38-MAP kinase [83,84], ERK [85] and IRAK [55] as well as TRIF, MyD88 and TRAF6 [86]. In addition, the PI3K/Akt pathway seems to play a specific role in platelet activation by aPLA.…”
Section: Internalization and Apla Receptorsmentioning
confidence: 99%
“…The 'two hit hypothesis' might provide a means to reconcile the controversy on the respective roles of TLR2 and TLR4. In this hypothesis TLR4 is required for inducing TLR2 expression on EC [24], while the constitutive expression of TLR2 in monocytes may lead to TLR4-independent results [20,[24][25][26][27]. Furthermore, the translocation of aPLA into late endosomes might contribute to their pathogenic effects [28][29][30].…”
Section: Introductionmentioning
confidence: 98%